Household and child food insecurity and CVD risk factors in lower-income adolescents aged 12–17 years from the National Health and Nutrition Examination Survey (NHANES) 2007–2016. Issue 4 (21st April 2022) - Fulay, Aarohee P; Vercammen, Kelsey A; Moran, Alyssa J; Rimm, Eric B; Leung, Cindy W
Abstract: Objective: Household food insecurity is associated with CVD risk factors in low-income adults, but research on these associations among adolescents is inconsistent. This study investigates whether household and child food insecurity is associated with CVD risk factors in lower-income adolescents. Design: Cross-sectional. Multivariable linear regression assessed the association between household and child food security and CVD risk factors. Household and child food security was measured using the US Food Security Survey Module. The analyses were adjusted for adolescent's age, sex, race/ethnicity, smoking status, physical activity and sedentary time, as well as household income and the head-of-household's education and marital status. Setting: The USA. Participants: The sample was comprised of 2876 adolescents, aged 12–17 years, with household incomes at or below 300 % federal poverty line from the National Health and Nutrition Examination Survey cycles 2007–2016. Results: The weighted prevalence of household food insecurity in the analytic sample was 33·4 %, and the weighted prevalence of child food insecurity was 17·4 %. After multivariable adjustment, there were no significant associations between household and child food insecurity and BMI-for-age Z -score, systolic and diastolic blood pressure, HDL-cholesterol, total cholesterol, fasting TAG, fasting LDL-cholesterol and fasting plasma glucose. Conclusions: Despite observed associations in adults, household food insecurity was not associated with CVD risk factors in a national sample of lower-income adolescents. Child food insecurity was also not associated with CVD risk factors. More research should be conducted to confirm these associations.